Does financial inclusion grease or sand the wheels of energy poverty in Africa? The role of governance and infrastructure - Godswill Osuma; Oluwatosin Oyetayo; Bankole Olajide Martins; Abieyuwa Ohonba (Sustainable Futures)
This study examines whether financial inclusion mitigates energy poverty in Sub-Saharan Africa, emphasising the moderating roles of governance quality and infrastructure. Drawing on panel data from 25 Sub-Saharan African countries between 2000 and 2023, our study employs Driscoll-Kraay Fixed Effects, System GMM, and Dynamic Panel Threshold models to ensure robust empirical validation. Our results show that financial inclusion alone does not significantly reduce energy poverty. However, interaction models reveal that financial inclusion effectively alleviates energy poverty when complemented by strong governance institutions and adequate electricity infrastructure. The Dynamic Panel Threshold analysis further supports these moderating influences, identifying critical governance and infrastructure thresholds above which financial inclusion significantly and negatively affects energy poverty. Conversely, in countries below these thresholds, the effect of financial inclusion is limited or statistically insignificant. The findings from the System GMM models also suggest high persistence in energy poverty, with limited evidence of significant interaction effects, underscoring the complexity of the relationship. Overall, the study concludes that financial inclusion is necessary but not sufficient on its own. Addressing energy poverty in Sub-Saharan Africa requires integrated strategies that improve governance effectiveness, scale energy infrastructure, and expand financial access.